(untitled) (Research, Society and Development, 2021)
Biodiesel has been highly promising in the partial or total replacement of petroleum-derived diesel oil and the methyl transesterification reaction is the most used route. However, the difference in polarity of the reactants causes difficulties in the homogenization of the reaction system, which can lead to yield losses. This problem can be minimized with the use of surfactants. The present work aims to prospect technologies for the use of surfactants as additives in biodiesel, based on a search in the patent filing database of the European Patent Institute (EPO) and the National Institute of Industrial Property (INPI). The research was carried out in July 2021, and patents filed between 2000 and 2020 were found and analyzed, considering a documentary study. It was possible to observe that the EPO’s database has more patents related to the subject than the INPI’s. In addition, most documents found in the EPO database has the classification code C10L1. The search in the EPO database showed that there is a significant number of patents in this area, distributed in 7 different countries, proving to be a very promising area for investments and technology development.